PTH-031 Pillcam sb2 and sb3 small bowel capsule endoscopy – comparisons and implications for practice. (22nd June 2015) - Dunn, S; Neilson, L; Davison, C; Butt, F; Panter, S
Abstract : Introduction: South Tyneside Hospital has been a referral centre for capsule endoscopy since 2005, performing over 1000 studies. We have previously shown that the diagnostic yield (DY) of the PillCam SB3 capsule (Given Imaging, Israel) is significantly higher than that of the PillCam SB2. 1 Here we present additional data on "learning curve" and offer suggestions for practice. Method: Previous work compared the DY of the last 100 SB2 capsules with the first 100 SB3s. To assess for a "learning curve" effect we reviewed our first 100 SB2 capsules (Oct 2007–Aug 2008). Indications, completion rates, small bowel recording times and pathology were recorded. Pathology was classed as significant if it related directly to indication. Results: 46 of the first 100 SB2 capsules were abnormal, of which 31 had significant pathology; almost identical to the last 100 SB2s (45 abnormal, 30 significant). Most tests (255/300, 85%) were for unexplained anaemia or Crohn's disease assessment. More capsules are now done for acute GI bleeding; 4 of the first 100 SB2 capsules, 12 of the last 100 SB2s and 15 of the first 100 SB3s. There were 23 incomplete SB2 capsules (11.5%) of which 18 (9%) were in small bowel at the end of recording and 5 were held up by pathology (2.5%). Only 5 SB3 studies (5%) were incomplete, with 4 (4%) not entering the colon and 1 (1%) held up by pathology. On average SB3 capsules had a longer recording time of 9 h and 24 min compared to 8 h and 2 min for the SB2s. Conclusion: 219 capsules were reported before the SB2 was introduced. Between the first hundred and last hundred SB2 capsules there were 1003 SB2 studies. This suggests that the increased DY is not due to a "learning curve", supporting our finding of increased DY with the SB3. Any "learning curve" is likely to be from the first 200 studies. Most studies are for iron deficiency anaemia and Crohn's disease assessment but there is a trend towards using capsules as a diagnostic tool in overt GI bleeds. Fewer SB3 studies were incomplete compared to SB2s. Our unit is now more proactive in monitoring gastric transit and colonic entry using the real time viewer and this change in practice may have helped with this. Longer recording times due to increased battery life may also play a part. We recommend monitoring capsules in real time and leaving the recorder on for longer if gastric transit is delayed or colonic entry is not clear. Disclosure of interest: None Declared. Reference: Dunn, S. et al . PTU-053 Is It Worth Repeating Previous Unremarkable Sb2 Capsules With The New Sb3? Gut 63 Suppl 1(2014):A61–A62